2001
DOI: 10.1089/108497801750096087
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Measurement of Apoptosis in Breast Cancer Cells Using99mTc-EC-Annexin V

Abstract: The results indicate that apoptosis can be quantified using 99mTc-EC-annexin and that it is feasible to use 99mTc-EC-annexin to image tumor apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 56 publications
2
47
0
1
Order By: Relevance
“…EC-Annexin V was prepared according to the previously described methods (17). Briefly, Sodium bicarbonate (1N, 1 ml) was added to a stirred solution of EC (5 mg, 0.019 mmol).…”
Section: Synthesis and Radiolabeling Of Ec-annexinmentioning
confidence: 99%
See 1 more Smart Citation
“…EC-Annexin V was prepared according to the previously described methods (17). Briefly, Sodium bicarbonate (1N, 1 ml) was added to a stirred solution of EC (5 mg, 0.019 mmol).…”
Section: Synthesis and Radiolabeling Of Ec-annexinmentioning
confidence: 99%
“…Using a standard coupling technique, 99m Tc-EC-drug conjugates were then developed to characterize tumor tissues (15,16). In the previous report, we have described in vivo biodistribution and planar imaging studies in tumor-bearing rats given 99m Tc-EC annexin V ( 99m Tc-EC-ANX), and have demonstrated the pharmacokinetic distribution of the tracer and feasibility of using 99m Tc-EC-ANX to image apoptosis-induced tumor (17). In this report, we demonstrate the imagings of 99m Tc EC-annexin V in women with PBC either before treatment (5 patients) or during the first cycle of IC (5 patients), and radiation dosimetry evaluation using image-based biodistribution analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A number of in vitro and in vivo studies have demonstrated that annexin V is a specific marker for early and late stages of programmed cell death [8][9][10][11][12][13]. Radioisotopelabeled annexin V is suitable for the detection of cell death induced by ischemia and reperfusion injury in the myocardium [14].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 We have previously reported a series of 99m Tc-EC-agent conjugates for functional imaging in oncology. [13][14][15][16][17][18][19][20] In addition, EC can also be labeled with 68 Ga for PET imaging and 188 Re (a beta and gamma emitter) for internal radionuclide therapy. 21-23 99m Tc, 68 Ga, and 188 Re are generator-produced isotopes that are accessible and affordable.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, 99m Tc-EC-DG (100 Ci) was incubated in dog serum (200 l) at 37°C at 0. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] hours. The serum samples were diluted with 50% methanol in water, and radio-TLC was used to analyze the product.…”
mentioning
confidence: 99%